2020
DOI: 10.1016/j.lanwpc.2020.100061
|View full text |Cite
|
Sign up to set email alerts
|

Presenting characteristics and clinical outcome of patients with COVID-19 in South Korea: A nationwide retrospective observational study

Abstract: Background: More than 13,0 0 0 cases were reported to be infected with COVID-19 by RT-PCR in South Korea. Most studies report clinical characteristics of hospitalized patients with COVID-19; the full spectrum of disease severity has thus not yet been well described.Methods: Using retrospective observational methods, this study analyzed factors affecting early clinical symptoms, clinical progress, and severity of disease for COVID-19 positive patients released from quarantine to provide information on establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
4
9
1
Order By: Relevance
“…The average age of the population studied was 53 years, which is a value higher than the series reported in Spain by Khan et al(2020), and in China by Bi et al(2020), and moderately higher than the South Korean series by Park et al(2020), and lower than the Italian series by Trecarichi et al(2020).…”
Section: Discussioncontrasting
confidence: 54%
“…The average age of the population studied was 53 years, which is a value higher than the series reported in Spain by Khan et al(2020), and in China by Bi et al(2020), and moderately higher than the South Korean series by Park et al(2020), and lower than the Italian series by Trecarichi et al(2020).…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, a study in Dakar, West Africa, revealed that about 14.7% of the COVID-19 cases have severe symptoms [ 48 ]. A lower percentage was observed in the severe (4.8%) and critical (0.6%) cases in the South Korean population involving 7803 COVID-19 patients and in the Thai population with a low prevalence rate of severe cases at 6.4% [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the association between the clinical characteristics such as older age, male sex, symptoms of COVID-19 (fever, cough, fatigue, and short of breath) and comorbidities (hypertension, diabetes, and CKD) and its severity or activity [24][25][26]. Addition of blood test may increase the accuracy of prediction of the disease progression [10].…”
Section: Discussionmentioning
confidence: 99%